The Role of Teachers and Parents in Addressing Students’ Habitual Tardiness at SD Muhammadiyah 01 Kandang Panjang, Pekalongan City - Moch Nur Soleh; Wiewiek Puji Astuti; Darsinah Darsinah; Wafrotur Rohmah (Journal of English Language and Education, 2026)
Student tardiness remains a persistent issue in elementary education, negatively affecting learning effectiveness, academic achievement, and character development. This study aimed to examine the roles of teachers and parents in addressing habitual tardiness among students at SD Muhammadiyah 01 Kandang Panjang, Pekalongan City. A qualitative descriptive approach was employed, involving the principal, classroom teachers, subject teachers, parents, and students selected through purposive sampling. Data were collected through observations, interviews, and documentation and analyzed using the interactive model of Miles, Huberman, and Saldaña. The credibility of the findings was ensured through source and method triangulation. The results revealed that student tardiness was influenced by internal factors, including poor time management, low self-discipline, weak learning motivation, and unhealthy sleeping habits, as well as external factors such as inadequate parental supervision, transportation constraints, and family routines. Teachers addressed these issues through discipline reinforcement, counseling, educational guidance, and positive reinforcement, while parents supported punctuality by establishing consistent daily routines and monitoring school preparation. Effective collaboration between teachers and parents through regular communication significantly improved student punctuality, highlighting the importance of school–family partnerships in fostering discipline and character development.